2012
DOI: 10.2528/pier12022010
|View full text |Cite
|
Sign up to set email alerts
|

Molding the Flow of Magnetic Field With Metamaterials: Magnetic Field Shielding

Abstract: Abstract-In this paper, it is demonstrated how anisotropic and inhomogeneous magnetic metamaterials may be used for molding the flow of the magnetic field, considering magnetic field shielding as the main application of practical interest. It is shown that using anisotropic materials, magnetic field shielding may be improved, and this anisotropy can be realized by metamaterials. Introducing additional inhomogeneity in the metamaterial can increase the shielding performance even more. The required parameters fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…It is clear that this method is highly effective and that should be the first one to be applied. However, if higher reduction is required, one should turn to additional procedures, like the use of shielding [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that this method is highly effective and that should be the first one to be applied. However, if higher reduction is required, one should turn to additional procedures, like the use of shielding [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Response of an RLC meta-atom: Phasors of the source (blue, continuous), resonator (red, dashed), and total (black, dotted) magnetic flux density. The circle is the trace of meta-atom magnetic flux density for frequencies from 0 to infinity [12]. M and N points show the points at which the total magnetic flux density is maximum and minimum respectively.…”
Section: Shielding Principle Of a Magnetic Meta-atommentioning
confidence: 99%
“…Since these regulations became stricter in some countries, e.g., Italy and Switzerland, there is a need for finding improved magnetic field shields. Recently, it has been shown that metamaterials can indeed be used to shield magnetic fields at very low frequencies [12]. Similar to natural materials, which are composed of atoms and molecules, metamaterials are composed of subwavelength units, which are called 'meta-atoms' [1].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently the studies on the shielding fabric have mainly focused on model construction of the BESF [3,4], performance of the BESF [5,6], testing of the BESF [7], and shielding fiber [8]. We still possess poor information about the SE computation of BESF.…”
Section: Introductionmentioning
confidence: 99%